2000
DOI: 10.1097/00007632-200007010-00010
|View full text |Cite
|
Sign up to set email alerts
|

Hematogenous Pyogenic Spinal Infections and Their Surgical Management

Abstract: Pyogenic spinal infection can be thought of as a spectrum of disease comprising spondylitis, discitis, spondylodiscitis, pyogenic facet arthropathy, and epidural abscess. Spondylodiscitis is more prone to develop epidural abscesses in the cervical spine (90%) than the thoracic (33.3%) or lumbar (23.6%) areas. Thecal sac neurocompression has a greater chance of causing neurologic deficit in the thoracic spine (81.8%). Treatment of neurologic deficit caused by epidural abscess is prompt surgical decompression, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

29
569
6
47

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 617 publications
(665 citation statements)
references
References 51 publications
29
569
6
47
Order By: Relevance
“…Our rough estimate of the incidence of SEA at 1.8/100,000 persons per year accords with other published estimates [1,2], although its appearance after only 1.1% of the spinal operations performed by our neurosurgical service seems less frequent than others have reported [8]. We found that the commonest pathogen causing SEA was Staphylococcus aureus, just as in other reports [4,5,12,13,15,21,22]. SEA is usually associated with one or more comorbidities [7]; the list of our patients' comorbidities resembles the corresponding lists in other reported series [4,5,8,12].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our rough estimate of the incidence of SEA at 1.8/100,000 persons per year accords with other published estimates [1,2], although its appearance after only 1.1% of the spinal operations performed by our neurosurgical service seems less frequent than others have reported [8]. We found that the commonest pathogen causing SEA was Staphylococcus aureus, just as in other reports [4,5,12,13,15,21,22]. SEA is usually associated with one or more comorbidities [7]; the list of our patients' comorbidities resembles the corresponding lists in other reported series [4,5,8,12].…”
Section: Discussionsupporting
confidence: 90%
“…SEA is usually associated with one or more comorbidities [7]; the list of our patients' comorbidities resembles the corresponding lists in other reported series [4,5,8,12]. The close association of chronic inflammatory diseases, endocarditis, and other septic conditions with SEA has already been pointed out [15], as has the risk of SEA in persons under immunosuppressive treatment [4,8,14]. SEA is known to become more common with advancing age because of the rising frequency of spinal disorders and of comorbidities [13], and the age distribution of our patients was similar to those previously reported [12,13].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations